The Potential Circular RNAs Biomarker Panel and Regulatory Networks of Parkinson’s Disease - Xiao, Yousheng; Chen, Hongchang; Liao, Jiajia; Zhang, Qinxin; He, Honghu; Lei, Jiang; Huang, Jinjun; Ouyang, Qiang; Shen, Yuefei; Wang, Jin (Frontiers in Neuroscience, 2022)
Parkinson's disease (PD) is a progressive neurodegenerative disease. It has been reported that circular RNAs (circRNAs) play important roles in several neurological diseases. However, the role and regulatory networks of circRNAs in PD are still largely unclear. In this study, we firstly compared the global expression level of circRNAs from PD patients and controls using microarray, then the candidate circRNAs were validated in another PD cohort. The possible functions of these candidate circRNAs were analysed using Gene ontology (GO) analyses and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyse, the regulatory networks of these candidate circRNAs were constructed through circRNA-miRNA-mRNA regulatory networks, protein-protein interaction (PPI) network as well as transcription factor-circRNA network. The results indicated that hsa_circRNA_101275, hsa_circRNA_103730 and hsa_circRNA_038416 were significantly higher expressed in PD patients, while hsa_circRNA_102850 was lower expressed in PD patients when compared with controls. A circRNA panel combining the four differentially expressed circRNA showed a high diagnostic ability to distinguish PD patients from controls (AUC = 0.938). Furthermore, GO and KEGG analysis showed these candidate circRNAs were enriched in PI3K−Akt and MAPK signaling pathway. We established a circRNA-miRNA-mRNA regulatory networks and identified 10 hub genes (ESR1, PTEN, SHC1, IGF1R, SMAD2, KRAS, MDM2, HIF1A, BMP4, ACVR2B) were closely related to PD by using PPI network analysis. Besides, these circRNAs were predicted to be regulated through tyrosine hydroxylase (TH) -relevant transcription factors such as GATA2 and GATA3. In conclusion, our results suggest the circRNA panel and the established circRNA-miRNA-mRNA regulation networks might provide potential novel biomarkers and therapeutic targets for PD.